PREVALENCE OF KELL BLOOD GROUP SYSTEM IN BLOOD DONORS ATTENDING A TERTIARY CARE CENTRE IN NORTHWESTERN INDIA - MATHURIA, GIRRAJ PRASAD; DADHICH, NARENDRA KUMAR; MEENA, BHEEM SINGH (International Journal of Current Pharmaceutical Research, 2024)
Objective: The Kell blood group system is amongst one of the clinically significant blood group system in blood transfusion, consisting of different types of antigens with high immunogenicity which can be a potential cause of serious transfusion reactions and hemolytic disease of fetus and newborn. Knowledge of the antigenic frequency is crucial to assess the risk of alloimmunisation and to guide the probability of finding antigen-negative donor blood, which can be useful for a patient with corresponding or multiple red cell alloantibodies. Methods: This is a retrospective study which was done at Department of Immunohematology and Transfusion medicine, SMS Medical College, Jaipur over a period of one year from 1st Jan to 31st Dec 2020. During the study period, blood both voluntary donors as well as replacement donors were typed for Kell antigens by automated red cell antigen typing by capture-R technology in neo immucor. Results: A Total of 9677(Nine Thousand Six Hundred Seventy Seven) Blood donors were typed for Kell Antigens. Out of these 9677 samples, 288 were Positive for Kell positive (K+) resulting in overall frequency of Kell (K) Antigen as 2.9%. Conclusion: This is the first study that set out to determine the prevalence of Kell antigens among Blood Donors in Northwestern India. These results appear to be useful in providing better care for patients by implementing tests that should become a routine in blood banks. The Kell system is very important in Transfusion medicine practice.